Evaluation of design elements in linear gardens in the municipality of Colima - Alcocer-García, Pablo; Preciado-Ochoa, Alexis Trinidad; Chung-Alonso, Peter; Correa-Fuentes, Dora Angélica; Rivera-Torres, Claudia (Estoa. Journal of the Faculty of Architecture and Urbanism, 2022)
The open public space of the linear garden type is not regulated in the Mexican national regulations; therefore, it is interesting to evaluate its spatial design through four themes (accessibility, environmental, furniture and safety), establishing the necessary characteristics for their evaluation through observation guides. The sample corresponded to three public spaces in the city of Colima (Paseo Turístico Río Colima, Santa Gertrudis and Ecoparque Manrique). As a result, a similarity was obtained among the gardens evaluated, positioning the Santa Gertrudis Linear Garden as the best evaluated despite not having the most recent intervention; in addition, problems related to the maintenance and safety of the spaces were identified, so that this evaluation provides guidelines for future intervention proposals that will help to generate safer and more accessible spaces for the population.